Morphological characteristics and phylogenetic analysis reveal Leccinum septentrionale sp. nov. (Boletaceae, Boletales) from China - Gao, Yue; Tong, Xin; Zhou, Hao; Yan, Hui-Fang; Hou, Cheng-Lin (Phytotaxa, 2024)
Leccinum belongs to the Boletaceae and has attracted attention from mycologists worldwide given their ecological and economic importance. China has a high diversity of macrofungi; however, Leccinum has not been thoroughly studied due to a lack of specimen collections with associated molecular data. In this study, based on morphological evidence and phylogenetic analysis of the nucleotide sequences of four loci (ITS, LSU, rpb2, and tef1-α), one new species of Leccinum is described from Beijing, China. Morphologically, Leccinum septentrionale is characterized by its pileus yellowish-brown to brown dirty orange maculae and larger basidia with 24–40(–44) × 10–17 μm in size. This study expands the species diversity of Leccinum in Beijing and furnished valuable data support for future systematic research on Leccinum.